Jake goes peanuts - Wright, Michael, 1954- (New York : Feiwel and Friends, 2010)
In an effort to get Jake to eat something other than peanut butter, his parents declare it "Peanut Butter Week" and create such dishes as peanut butter soup, peanut butter pot roast, and even peanut butter dog food for their pet.
Keywords: Stories in rhyme; Peanut butter -- Fiction; Eating customs -- Fiction